2011
DOI: 10.3109/0142159x.2011.565829
|View full text |Cite
|
Sign up to set email alerts
|

Effects of partial substitution of pre-clinical skills training by attachments to primary health care centers: An experimental study

Abstract: Background: Recent studies indicate that students may encounter problems when they have to apply clinical skills learned in a skills laboratory to patients. To facilitate this transition, it has been advised to include patient contacts early in the pre-clinical curriculum. Objective: To compare clinical skills performance and level of preparedness for entering the clerkships between students who were prepared exclusively in a skills laboratory and peers for whom part of their skills training program was substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…On the other hand, ECE seems more efficient to improve preparation of pre-clinical students for their clinical rotations than considerable expansion of the skills laboratory training program. This may be particularly important in developing countries where budget restrictions call for the selection of the most cost-efficient solutions [11]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, ECE seems more efficient to improve preparation of pre-clinical students for their clinical rotations than considerable expansion of the skills laboratory training program. This may be particularly important in developing countries where budget restrictions call for the selection of the most cost-efficient solutions [11]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we demonstrated that pre-clinical students who were trained in PHC centers felt better prepared for entering their clerkships. [11]. For this study, the same students involved in the previous one were interviewed for this study after they had entered the clinical phase of their studies.…”
Section: Introductionmentioning
confidence: 99%
“…Taiwan's medical training consists of 7 years of post-secondary medical school followed by Effects of a new parallel primary healthcare centre and on-campus training programme on history taking, physical examination skills and medical students' preparedness: a prospective comparative study in Taiwan Ying-Ying Yang, 1,2,3 Shuu-Jiun Wang, 1,4 Ling-Yu Yang, 1,5 Jiing-Feng Lirng, 1,4 Chia-Chang Huang, 1,2 Jen-Feng Liang, 1,5 Fa-Yauh Lee, 1,3,4 Shinn-Jang Hwang, 1,4 Chin-Chou Huang, 1 ► Similar preparation period before assessments, as well as randomised raters, simulation patients, students and standardised processes in group objective structured clinical examination (GOSCE)/ OSCE ensured the comparability of the results of the primary healthcare centre (PHCC) group and the PHCC training in combination with on-campus history taking (HT) and physical examination (PE) training (PHCC+on-campus) group. ► Pre-clerks in both modules, which equally extended the whole fourth year of medical education, were volunteers that were more committed, brighter and motivated; this may have resulted in some degree of selective bias.…”
Section: Introductionmentioning
confidence: 99%
“…Hence a well organised IM orientated preclinical skills curriculum is crucial for enhancement of students' future comfort and confidence with PHCC patients and hospital inpatients during their clinical clerkship. 5 Nonetheless, recent studies have suggested that the HT and PE skills of clinical clerks is already below expectation at the end of the IM clerkship and residency. [6][7][8] Accordingly, this study aims to evaluate the effectiveness of parallel on-campus, faculty led, student assisted training and PHCC basic HT and PE skills training courses on pre-clerks' preparedness for IM clerkship, especially confidence/coping, patient management and self-directed learning.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate students may encounter problems when applying clinical skills learned in a skills laboratory to actual patients. To facilitate this transition, it has been recommended that medical schools include patient contact early in the preclinical curriculum [10]. However, few studies show students' early clinical skill development is not influenced by the educational setting [11].…”
Section: Discussionmentioning
confidence: 99%